The effect of Market Orientation on Export Performance: The Mediating role of New Product Development capability - Wakjira, Gada Gizachew (Adpebi International Journal of Multidisciplinary Sciences, 2023)
The aim of this study that titled the descriptive statistics of Market Orientation practice on Export Performance the Mediating role of new product development practice with Positive effect of export performance provides firms with opportunity to grow, and enhance the dynamism in the new product development. In this study, two main strategies that are refer to Market Orientation and new product development is investigated and determines the Export Performance. This study focused in Coffee trading and Factory PLC Ethiopia. The findings showed that the Descriptive effect of Market Orientation on Export Performance the Mediating role of New Product Development Capability. However, the market orientation is much stronger in influence the export performance that affect Market orientation through new product development on Export performance, it designed with Descriptive Statistics to distribute for 384 respondents, and the questionnaires to be distributed from Primary and Secondary Cooperative Union, Coffee supplier, Coffee Collector, Employee of PLC. Hence, this study basically increased the knowledge regarding of the factors that affect the Export Performance, especially in Oromia Regional state West Guji zone Coffee trading and Factory PLC, Ethiopia.